1999
DOI: 10.1177/014556139907800707
|View full text |Cite
|
Sign up to set email alerts
|

Xerostomia: A Prevalent Condition in the Elderly

Abstract: Although xerostomia is associa ted with aging, studies have dete rmined that salivary gland f unction is well preserved in the healthy geriatric population. Theref ore, dry mouth is probably not a condition ofaging, but most likely one ofsystemic or extrinsic origin. Saliva seems to undergo chemical changes with aging. As the amount of ptyalin decreases and mucin increases, saliva can become thick and viscous and prese nt problems fo r the elderly. One of the most prevalent causes of xeros tomia is medication.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
9

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(73 citation statements)
references
References 15 publications
1
63
0
9
Order By: Relevance
“…The feeling or evidence of dry mouth in these individuals is more likely due to the side-effects of anticholinergics, psychotropic drugs, antihistamines and or diuretics. [13] There have been several studies that have shown clear alterations in the quality and quantity of saliva in BMS affected individual.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The feeling or evidence of dry mouth in these individuals is more likely due to the side-effects of anticholinergics, psychotropic drugs, antihistamines and or diuretics. [13] There have been several studies that have shown clear alterations in the quality and quantity of saliva in BMS affected individual.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Third, we will determine whether YMJ can change the subjective feeling of dry mouth as well as the salivary flow rate. Although the relationship between a subjective feeling of dry mouth and the salivary flow rate is controversial [8,9,37], the change in these factors in association with YMJ treatment could be compared in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the elderly, the long-term use of medications and aging are regarded as major causes of xerostomia [9]. However, recent xerostomia studies mostly focused on Sjögren’s syndrome or postradiotherapy-induced xerostomia, which are related to salivary gland damage, and only a few studies have assessed xerostomia in elderly subjects who did not exhibit obvious structural damage of the salivary glands [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…cGVHD damages both the oral mucosa and the salivary glands. Salivary gland involvement in cGVHD is characterized by reduced salivary secretion and xerostomia (2-4). Common areas of mucosal cGVHD involvement are the tongue, buccal and labial mucosae (5,6).…”
Section: Introductionmentioning
confidence: 99%